PERAMALAN PERMINTAAN PRODUK ROTI PADA INDUSTRI âTIARA RIZKIâ DI KELURAHAN BOYAOGE KECAMATAN TATANGA KOTA PALU - Gusdian, Eby (AGROTEKBIS, 2016)
This study aimed to forecast demand for bakery products at âTiara Rizkiâ industry in Boyaoge Village Tatanga District of Palu City in 2016. This research was conducted in June 2015. The respondent in this research are the owner and 2 employees of âTiara Rizkiâ Industry. The used data was from Primary and secondary data. The Analysis tool are Single Moving Average and Single exponential smoothing. The result showed that the forecast for September was 31,835 pack, with the Mean Absolute Error by 2,005 and Mean Squared Error by 17,243,400.Â Result in September also can determine prediction in 2016. The calculation using Exponential Smoothing the Î± is 0.9, Mean Absolute Error is 2,912 and Mean Squared Error is 24,087,750, which Mean absolute Error and Mean Squared Error were the smallest.